The impact of an antenatal resilience and optimism workshop on postnatal depressive symptoms - Ratna, Josephine Maria Julianti (Curtin University, 2015)
Eight primary health care clinics in Surabaya, Indonesia were randomised to intervention or waitlist-control group. Second trimester pregnant women from the clinics were grouped accordingly. The impact of a 2-day Antenatal Resilience and Optimism Workshop (AROW) showed significant increases in resilience and life satisfaction and reduction in depression, anxiety and stress for the intervention group, maintained at 6 months postintervention. AROW is recommended as an antenatal program in Indonesia and possibly in other developing countries.